Helicobacter pylori Infection and Autoimmune Thyroid Diseases: The Role of Virulent Strains - Natale Figura; Giovanni Di Cairano; Elena Moretti; Francesca Iacoponi; Annalisa Santucci; Giulia Bernardini; Stefano Gonnelli; Nicola Giordano; Antonio Ponzetto (MDPI AG, 2019)
Aim: To verify a possible association between overall H. pylori and CagA+ H. pylori infection and autoimmune thyroid diseases (AITDs). Methods: Consecutive patients with AITDs admitted to one single centre of Endocrinology during one solar year were examined. The diagnoses were Hashimoto thyroiditis (HT) in 76, Graves’ Disease (GD) in 39, and aspecific thyroiditis (AT) in 44 patients. Controls were 136 individuals without AITDs. Median values of fT3, fT4, anti-thyreoglobulin (Tg) antibodies, IL-1β, IL-6, and TNF-α in patients were compared with those in controls. H. pylori infection and CagA status were determined serologically. Structural homology of some thyroid proteins with H. pylori antigens was investigated. Results: H. pylori infection prevalence was significantly increased in GD (66.6%) and HT (64.4%) patients, vs. 29.4% of controls and 34.0% of AT. CagA seropositivity was significantly more frequent in GD (46.1%) and HT (46.9%) infected patients, vs. infected controls (20%). fT3 and fT4 median values were significantly decreased in infected CagA+ GD patients vs. uninfected GD patients. IL-1β median values were increased in patients respect to controls, independently of the clinical form of AITD. Median values of IL-6, TNF-α and anti-Tg autoantibodies in CagA infected patients were significantly higher than those measured in infected CagA− and uninfected patients and in infected CagA+ controls. The examined thyroid proteins shared putative conserved domains with numerous bacterial antigens. Conclusions: Overall H. pylori and CagA+ H. pylori infection were associated with GD and HT, putatively through an increased inflammatory status and molecular mimicry.